THE EFFECTIVENESS OF UVAERATOR IN REDUCING AIR GERMS AND DUST LEVELS - Tri Cahyono; Teguh Widiyanto (Poltekkes Kemenkes Semarang, 2020)
Background, school education facilities, including higher education as a place and public facilities for formal education facilities in this country, should be a comfortable place to study. Besides functioning as a place of learning, schools can also be a threat of disease transmission . measurement number of bacteria in the air-conditioned classrooms Wulan R22 (2016) 12.167 CFU / m3 , Nur Latifah (2018) an average of 217.92 colony / hr / ft2 , hadita (2018) 331.6 colonies / hr / ft2 . Research question is how is the effectiveness of UVAerator in reducing the number of air germs and dust levels in the lecture hall R22 building Campus 7 Poltekkes Kemenkes Semarang ? Research objectives is to find the effectiveness of UVAerator in reducing the number of air germs and dust levels in the lecture hall. Research method included a quasi-experimental design with a non-equivalent control group pre test - post test. Data collection by measuring, observational, interview. The variables were temperature, humidity, lighting, air germ count, dust content. Analysis using pairet-t test comparisons and unpaired t test data. Result, the average number of bacteria with no air space UVAerator in the morning is ( 668,00 g / m3 ) and in the afternoon is ( 680.10 g / m3 ) the difference was not significant (p = 0.873), whereas the existing space UVAerator in the morning ( 876.50 g / m3 ) and in the afternoon ( 655.50 g / m3 ) shows significant difference (p = 0.001). The number of room air germs that do not exist and have UVAerator is significantly different (p = 0.002), the number of room air germs that are not there and without any UVAerator is not significant (p = 0.763), while the change in the number of room air germs that does not exist and exist UVAerator has a significant difference (p = 0.015). On average PM10 space dust that has no UVAerator in the morning ( 12.38 ug / m3 ) and in the afternoon ( 17.38 ug / m3 ) shows significant difference (p = 0.008), whereas the existing space UVAerator in the morning ( 11.63 g / m3 ) and day ( 14.50 µg / m3 ) shows that the difference is not significant (p = 0.127). PM10 dust in the room that does not exist and there is no UVAerator ported, the difference is not significant (p = 0.821), the PM10 dust in the room noon and there is UVAerator, the difference shows that it is not significant (p = 0.432), while the change in room PM10 without dust and there is a difference in UVAerator significant (p = 0.004). In conclusion, the effectiveness of reducing the number of air germs without UVAerator on average (4.56%), with UVAerator (-24.52%), the difference was not significant (p = 0.057). The effectiveness of reducing PM10 without UVAerator, mean (60.50%), with UVAerator (38.30%), the difference was not significant (p = 0.369). Suggestion, , It is necessary to control the sound intensity caused by UVAerator by adding aeration bubble breakers. The pump suction power is enlarged to accelerate the circulation of room air.